Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah, Standar Akuntansi Pemerintahan, dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi pada Organisasi Perangkat Daerah Kota Bukittinggi) - Putra, Dasmi; Salfadri, Salfadri; Lady Silvera, Dica (Ekasakti Pareso Jurnal Akuntansi, 2024)
This study aims to  examine the  effect of  applying the regional financial accounting system, government accounting standards and human resource competence on the quality of local government financial reports (study in the local government organization of Bukittingi City). Research respondents are the Head of Service, Head of Financial Management and Staff of 28 Regional Apparatus Organizations in Bukittinggi City. Meanwhile, the total sample was 84 which was determined by purposive sampling. The technique in collecting data is through a questionnaire. Then the technique for analyzing the data in this study is multiple linear regression using SPSS 25. The study found that the application of the regional financial accounting system showed a significant influence on the quality of local government financial reports. Likewise, government accounting standards and human resource competencies show a significant influence on  the  quality of  local  government financial  reports.  Simultaneously, it  was  found  that  the application  of  regional  financial  accounting  systems,  government  accounting  standards  and human resource competencies significantly affected the quality of local government financial reports.